Preparation and conformation of Arabinofuranosyl pyridinium salts and hydrolysis of the bromoisoquinolinium compound - Wijesundera, W.S.S. (Elsevier, 1985)
Tri-O-benzoyl-α-l-arabinofuranosylpyridinium salts can be made inacceptable yields and high stereochemical purity by the reaction of 2,3,5-tri-O-benzoyl-α-l-arabinofuranosyl bromide and the pyridine in the presence of tetrabutylammonium bromide. Analysis of the 1H-n.m.r. signals of the sugar reveals that the benzoylated compounds adopt largely the E2 conformation whereas the debenzoylated compounds are largely in the oT1 conformation. The α-l-arabinofuranosyl-4-bromoisoquinolinium ion hydrolyses by both pH-independent and base-catalysed pathways, complicated by the reversible formation of an inert pseudo-base in alkali. The comparatively low rate of the pH-independent reaction is discussed in terms of the acid-lability of furanosides.